PENGARUH PEMBERIAN PUPUK KANDANG KAMBING TERHADAP PERTUMBUHAN TANAMAN KANGKUNG DARAT (Ipomoea reptans) PADA TANAH MARGINAL - Finidi S. B. R. Walangitan; Joice M. Supit; Rafli I. Kawulus (Universitas Sam Ratulangi, 2021)
ABSTRACT This research aimed to observe the effects of distributing goat manure on marginal soils with indicators of water spinach. It was conducted in pot experiment using goat manure treatment which consist of 0 ton/acre as control, 10 ton/acre; 20 ton/acre; 30 ton/acre and Phonska 300 kg/acre. There were 2 plants per hole. Incubation period of the goat manure was 2 weeks long. This research was done in 2 month. Research method used was a Completely Randomized Design (CRD) and 3 repetitions. Variabels analyzed were plant height, number of leaves, and wet basis of water spinach. Statistical test for the tabulated data was run by using Analysis of Variance (Anova) and Least Significant Difference (LSD). The result of this research showed that goat manure treatment has no real affect on the plan height, number of leaves and wet basis of water spinach, but there is a tendency from each goat manure treatment. Keywords : Goat Manure, Kangkung Darat, Marginal Land